Assessing the reporting quality of randomized controlled trials on COVID-19 vaccines: a systematic review - Guanran Zhang; Sirui Kuang; Xiaoli Zhang (Taylor & Francis Group, 2022)
This systematic review evaluated the reporting quality of COVID-19 vaccine randomized controlled trials (RCTs). Relevant RCTs published between July 20, 2020 and June 11, 2021 were identified in the PubMed database by two independent reviewers. Study quality was evaluated with the 2010 AND 2001 Consolidated Standards of Reporting Trials (CONSORT) adherence scores. A total of 22 RCTs were included. The median CONSORT adherence score according to the 2010 criteria was 21 (range, 12-25), thus indicating that 75% of the items in more than half of the RCTs had clear reports. Univariate analysis showed that CONSORT adherence scores were not predicted by category; analysis of variance also showed no significant difference between groups. Our results indicated that the overall quality of COVID-19 vaccine RCTs was very good. Current evidence indicates that a variety of COVID-19 vaccines are effective. No RCTs have reported serious adverse effects such as mortality.